AN ASSESSMENT OF THE ROLE OF ABO BLOOD GROUP ON MALARIA INFECTION IN A HETEROGENOUS COMMUNITY, KADUNA – NIGERIA: ABO blood group and malaria - Salman, Abdulmalik Abdullahi; Ibrahim, Halima Sadiya; Abdullahi, Aliyu Dantani; Usman, Aliyu Mohammed; Shuaibu, Mohammed Nasir (FUDMA Journal of Sciences, 2025)
Malaria is a global public health concern considered a leading cause of morbidity. A cross-sectional study was carried out to assess the role of ABO blood group on malaria between April and June 2024. A total of 120 blood samples were collected from patients aged five and above, except pregnant women undergoing malaria test at Primal Diagnostic Service in Kaduna state. Blood samples were collected from patients and stained with Field stain using standard parasitological techniques. Agglutination techniques using monoclonal anti-sera A, B and D were used to determine the ABO blood groups and a full blood count analysis was carried out to check some hematological parameters. Data generated was analysed using ANOVA test and statistical significance level was set at P<0.05. An overall malaria prevalence observed showed 53.3% and 30% of the study population had low and moderate malaria parasite densities respectively. About 42.5% and 40% of the population were females and males respectively with malaria parasites. The population of blood group O (43%) patients was higher compared to A (25%), B (18%) and AB (14%) groups respectively. Similarly, group O had the most number of confirmed malaria parasitaemia of 41.4% followed by groups A, B and AB with 26.3%, 16.2% and 16.2% respectively. There was a significant decrease P<0.05 in red blood cell count of malaria-infected patients which was pronounced in blood group O compared to the other blood groups. Data from this study does not show variation in RBC counts in ABO blood group during malaria.